INA complex liaises the F1Fo-ATP synthase membrane motor modules. Issue 1 (December 2017) - Naumenko, Nataliia; Morgenstern, Marcel; Rucktäschel, Robert; Warscheid, Bettina; Rehling, Peter
Abstract The F1 F0 -ATP synthase translates a proton flux across the inner mitochondrial membrane into a mechanical rotation, driving anhydride bond formation in the catalytic portion. The complex's membrane-embedded motor forms a proteinaceous channel at the interface between Atp9 ring and Atp6. To prevent unrestricted proton flow dissipating the H+ -gradient, channel formation is a critical and tightly controlled step during ATP synthase assembly. Here we show that the INA complex (INAC) acts at this decisive step promoting Atp9-ring association with Atp6. INAC binds to newly synthesized mitochondrial-encoded Atp6 and Atp8 in complex with maturation factors. INAC association is retained until the F1 -portion is built on Atp6/8 and loss of INAC causes accumulation of the free F1 . An independent complex is formed between INAC and the Atp9 ring. We conclude that INAC maintains assembly intermediates of the F1 F0 -ATP synthase in a primed state for the terminal assembly step–motor module formation. The inner membrane assembly complex (INAC) interacts with components of the F1 F0 -ATP synthase but its function remains unclear. Here the authors show that INAC associates with two distinct complexes during F1 F0 -ATP synthase formation, which points towards a safeguarding role during proton-conducting channel assembly.